Analisis Tekstual Wacana Korupsi: Penggunaan Diksi untuk Kata Kunci dan Ciri Korupsi - Manurung, Rosida Tiurma (Zenit, 2014)
This study is entitled " Analysis of Textual Corruption in Mass Media Discourse: A Critical Discourse Analysis Study ". This study uses qualitative with descriptive data presentation. The main theory used in this study is Critical Discourse Analysis of Three Dimensional Norman Fairclough focused only on the analysis of micro-level (textual). Meanwhile, supporters of the theory are the labeling theory, and the theory of the value of the expression. The data of this study consist of fourteennews discourses derived from the seven themes of corruption discourse published in the mass media throughout the 2011-2014 Detik.com. The discourse data are Bribery Case of Athletes Building Palembang, Social Aid Fund Fraud Case in Bandung, Bribery Case of Athletes Building in Hambalang, SKK Gas Bribery Case, SIM Simulator Inflation Fund Case, Bribery Case of Beef Export Quotas, and Chief Justice Bribery Case. This study aims to analyze and describe the diction.Keywords: Critical Discourse Analysis, analysis of micro-level (textual), corruption discourse.